KONTRIBUSI KERJA WANITA DALAM KELUARGA PETANI AREN DI DESA RAMBUNAN DAN SAWANGAN KECAMATAN SONDER - Selvie Martha Momuat; Ventje V. Rantung; Wilson M. Wangke; Charles R. Ngangi (COCOS, 2013)
ABSTRACTThis study aims to determine the contribution of working women in palm sugar farm inthe village of Rambunan and Sawangan Sonder subdistrict. Implementation lasts longer than 3(three) months from May 2012 to July 2012 in the Rambunan and Sawangan VillageSubdisttrict of Sonder Minahasa District. The sample collecting by purposive sampling with thenumber of respond is 40 women farmer. Data were analyzed descriptively and are presented intabular form.The results of this research showed the contribution of working women in the palm sugarfarming family in the Rambunan and Sawangan village more devoted to work in farming thanoutside of farming. This is evident from the percentage of total working time of women infarming palm sugar in those villages which shows the results greater than jobs outside palmsugar farm.Based on an average flow of time and the percentage of women working in farming palmsugar obtained showed the greatest results, the contribution of the highest female labor in palmsugar farms in the Rambunan and Sawangan village is the sales activities (print sugar).Contribution of working woman in palm sugar farming activities in the rambunan andsawangan is the filtering activities with average of time obtained from the event shows thesmallest results.Suggested considering women workers in palm sugar farming give contributes largeenough, Processing of farm products more developed (variable) to increase farm family incomeand be able to utilize labor from outside the family, so the women farmers with her family willalso be increased. Needs to be continue, especially regarding the effect of contribution of theworking women to farm families income.